Empathy and Perceptions of Spirituality and Spiritual Care Among Turkish Nursing Students: A Correlational Study - Tuğba Gözütok Konuk; Gizem Nur Katı (Artuklu Health)
Introduction: This study aimed to determine the relationship between nursing students' levels of empathy and their perceptions of spirituality and spiritual careMethods: This descriptive, correlational study included a sample of 401 nursing students in their second, third, and fourth years at a state university’s nursing faculty. Data were collected using the Introductory Information Form, the Toronto Empathy Scale, and the Spirituality and Spiritual Care Rating Scale.Results: The students' mean total score on Toronto Empathy Scale was 54.26 ± 6.75, and their mean total score on Spirituality and Spiritual Care Rating Scale was 65.88 ± 7.99. A significant difference was found between the total Toronto Empathy Scale scores and variables such as gender, receiving education on spirituality and spiritual care, and the need for education on spiritual care (p